Domino insertion-coupling synthesis of solid-state luminescent propynylidene indolones - Schönhaber, Jan; D'Souza, Daniel M.; Glißmann, Tobias; Mayer, Bernhard; Janiak, Christoph; Rominger, Frank; Frank, Walter; Müller, Thomas J. J. (Chemistry - a European journal, 2018)
Abstract The compound class of 3-arylpropynylidene indolones, key intermediates in consecutive three-component syntheses of various indole-based chromophores with peculiar emission characteristics, are readily synthesized by a domino insertion?coupling synthesis with an electronically diverse substitution pattern in moderate to excellent yields. The title compounds are formed in E/Z-ratios from 100:0 to 0:100. Besides structure elucidation by NMR-spectroscopy and X-ray structure analysis, DFT calculations have been employed to rationalize the observed stereoselectivity. The photophysical properties of 3-arylpropynylidene indolones are characterized by intense, tunable, solid-state emission of N-substituted derivatives as quantified for drop-cast films. The electronic ground state structure was corroborated by DFT and TD-DFT calculations, showing that gradient-corrected exchange and correlation PBE (Perdew?Burke?Ernzerhof) functionals can be successfully employed to correctly reproduce the observed absorption characteristics of merocyanine derivatives. The huge Stokes shifts strongly depend on the electronic substitution pattern as supported by Hammett?Taft correlations.
Gesehen am 22.04.2020